WORKSHOP PEMBUATAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS VIDEO SCRIBE SEBAGAI ALTERNATIF PEMBELAJARAN DARING - Rani Refianti; Idul Adha; As Elly AS; Anna Fauziah (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2021)
Workshop activities on making learning media for mathematics learning media based on Video Scribe as an alternative online learning for teacher working groups produce simple teacher-made learning media that can be used during learning during the current pandemic. Based on the results of the questionnaire analysis on the practicality of the workshop on making video scribe-based mathematics learning media as an alternative online learning for the teacher working group for the first indicator, a score of 56 was obtained with a percentage of 73.68%, for the second indicator a score of 64 was obtained with a percentage of 84.21%, for the third indicator a score of 60 was obtained with a percentage of 78.94%, for the fourth indicator a score of 59 was obtained with a percentage of 77.63%, for the fifth indicator a score of 70 was obtained with a percentage of 92.10%, for the sixth indicator a score of 66 was obtained with a percentage of 86.84 %, and for the seventh indicator, a score of 72 was obtained with a percentage of 94.73%. Overall, the average score of the practicality of the workshop on making video scribe-based mathematics learning media as an alternative online learning for the teacher working group was 84.01% in the good category.